The Influence Of Employee Leadership And Discipline On Improving Service Qualityto The Community At The Village Officedwitiro Bontotiro District Bulukumba District - Siswan, Siswan; Ahmad, Ahmad; Samsul Rizal (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to analyze the extent of the influence of employee leadership and discipline on improving the quality of community services at the Dwitiro Village Office, Bontotiro District, Bulukumba Regency." As well as to analyze the variables that most dominantly influence the quality of service at the Dwitiro Village Office, Bontotiro District. To apply this objective, the multiple regression analysis method is used. Based on the results of the regression, the equation Y= -5.535 + 0.807 X_1+ 0.329 X_2+ e. From the results of the analysis model between leadership and discipline, it shows that there is a significant relationship in service quality because R^2 = 0.741, which means that there is a fairly strong influence between leadership and discipline on service quality at the Dwitiro Village Office, Bontotiro District, Bulukumba Regency.